The diagnostic value of circulating tumor DNA in hepatitis B virus induced hepatocellular carcinoma: a systematic review and meta-analysis - Young Chang; Soung Won Jeong; Jae Young Jang; Hyuksoo Eun; Young‑Sun Lee; Do Seon Song; Su Jong Yu; Sae Hwan Lee; Won Kim; Hyun Woong Lee; Sang Gyune Kim; Seongho Ryu; et al. (Korean Liver Cancer Association, 2022)
Background/Aim New biomarkers are urgently needed to aid in the diagnosis of early stage hepatocellular carcinoma (HCC). We performed a meta-analysis on the diagnostic utility of circulating tumor DNA (ctDNA) levels in patients with hepatitis B virus-induced HCC. Methods We retrieved relevant articles from PubMed, Embase, and the Cochrane Library up to February 8, 2022. Two subgroups were defined; one subset of studies analyzed the ctDNA methylation status, and the other subset combined tumor markers and ctDNA assays. Pooled sensitivity (SEN), specificity (SPE), positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and area under the summary receiver operating characteristic curve (AUC) were analyzed. Results Nine articles including 2,161 participants were included. The overall SEN and SPE were 0.705 (95% confidence interval [CI], 0.629-0.771) and 0.833 (95% CI, 0.769-0.882), respectively. The DOR, PLR, and NLR were 11.759 (95% CI, 7.982-17.322), 4.285 (95% CI, 3.098-5.925), and 0.336 (0.301-0.366), respectively. The ctDNA assay subset exhibited an AUC of 0.835. The AUC of the combined tumor marker and ctDNA assay was 0.848, with an SEN of 0.761 (95% CI, 0.659-0.839) and an SPE of 0.828 (95% CI, 0.692-0.911). Conclusions Circulating tumor DNA has promising diagnostic potential for HCC. It can serve as an auxiliary tool for HCC screening and detection, especially when combined with tumor markers.